Influence of larger graft weight to recipient weight on the post‐liver transplantation course. (7th January 2013) - Levesque, Eric; Duclos, Julie; Ciacio, Oriana; Adam, Rene; Castaing, Denis; Vibert, Eric
Abstract: Size matching between recipient and donor livers is an important factor in organ allocation in the context of liver transplantation (LT). The aim of this study was to determine whether a large graft for recipient size influenced the post‐transplant course. One hundred and sixty‐two successive LT recipients were included and retrospectively divided into two groups: 25 (15%) had a graft‐to‐recipient weight ratio (GWRW) ≥2.5% and 137 (85%) had a GWRW <2.5%. Postoperative complications and outcomes were recorded. In the GWRW >2.5% group, more end‐to‐end caval replacement (72% vs. 38%, p = 0.003) and veno‐venous bypass (48% vs. 23%, p = 0.01) were used. Peak AST/ALT values were higher in the GWRW >2.5% group (AST: 596 [70–5876] vs. 453 [29–5132] IU/l, p = 0.03; ALT: 773 [101–5025] vs. 383 [36–4921] IU/l, p = 0.02). Among postoperative complications, the rate of respiratory failure was higher in the GWRW >2.5% group (32% vs. 14%, p = 0.04). The rates of other complications did not differ between the two groups. Both groups had similar graft and patient survival rates at one yr. Using large grafts for recipient size did not impair liver function and did not modify graft and patient outcomes at one yr. However, a GWRW >2.5% appeared to be a determining factor for respiratory morbidity following LT.